Blood plasma phosphorylated-tau isoforms track CNS change in Alzheimer’s disease - Barthélemy, Nicolas R.; Horie, Kanta; Sato, Chihiro; Bateman, Randall J. (The Journal of experimental medicine, 2020)
Highly sensitive and specific plasma biomarkers for Alzheimer’s disease (AD) have the potential to improve diagnostic accuracy in the clinic and facilitate research studies including enrollment in prevention and treatment trials. We recently reported CSF tau hyperphosphorylation, especially on T217, is an accurate predictor of β-amyloidosis at asymptomatic and symptomatic stages. In the current study, we determine by mass spectrometry the potential utility of plasma p-tau isoforms to detect AD pathology and investigate CSF and plasma tau isoforms’ profile relationships. Plasma tau was truncated as previously described in CSF. CSF and plasma measures of p-tau-217 and p-tau-181 were correlated. No correlation was found between CSF and plasma on total-tau levels and pS202 measures. We found p-tau-217 and p-tau-181 were highly specific for amyloid plaque pathology in the discovery cohort (n = 36, AUROC = 0.99 and 0.98 respectively). In the validation cohort (n = 92), p-tau-217 measures were still specific to amyloid status (AUROC = 0.92), and p-tau-181 measures were less specific (AUROC = 0.75).